Investigation of healing effects of Afyonkarahisar Region thermal spring water on experimentally-induced nephritis in mice - Bülent Elitok; Agilonu Yasin; Yavuz Ulusoy; Bahadır Kilinç (Ветеринария сегодня)
The aim of this study was to determine the efficacy of Afyokarahisar termomineral water in the treatment of nephritis. For this purpose, 40 Albino mouse at the same daily age were used. Nephritis was induced by adding adenine to their feed at a rate of 0.2% for 6 weeks. After nephritis was induced, a 21-day treatment period was started, and the mice were equally divided into two groups as control and study. While control group mice were received tap water daily and bathing in tap water, study group animals were given fresh Süreyya I hot spring water daily and bathing in this water. Clinical, hematological, blood biochemical and histopathological examinations were performed before the study, after nephritis formation, and on days of 1st, 7th, 14th and 21st of treatment period. Results of this study showed that WBC, NEUT and MCV levels increased significantly (p < 0.05) following nephritis formation, while RBC, HB, HCT, LYM, MCH and MCHC levels decreased significantly (p < 0.05). It was also determined that AST, GGT, GLU, BUN and IgG levels of blood biochemical parameters were significantly increased (p < 0.05) and TP, ALB levels decreased significantly (p < 0.05) after nephritis formation. At the end of the study, it was seen that all the measured parameters turned to the normal range in the study group animals, whereas problems still continuing with control group animals. Consequently, it was concluded that Süreyya I hot spring water was very successful in the treatment of nephritis and considered as an option in the treatment of nephritis.